Higher circulating EGF levels associate with a decreased risk of IgE sensitization in young children - DIABIMMUNE Study Grp; Reinert-Hartwall, Linnea; Siljander, Heli; Härkönen, Taina; Vatanen, Tommi; Ilonen, Jorma; Niemelä, Onni; Luopajärvi, Kristiina; Dorshakova, Natalya; Mokurov, Sergei; Peet, Aleksandr; Tillmann, Vallo; et al. (Pediatric Allergy and Immunology, 2022)
Background Decreased exposure to microbial agents in industrialized countries and urban living areas is considered as a risk factor of developing immune-mediated diseases, such as allergies and asthma. Epithelial surfaces in the gastrointestinal and respiratory tracts and in the skin constitute the primary areas in contact with the environmental microbial load. Methods We analyzed the levels of 30 cytokines and growth factors in serum or plasma as markers of the immune maturation in the participants in the DIABIMMUNE study from Russian Karelia (n = 60), Estonia (n = 83) and Finland (n = 89), three neighboring countries with remarkable differences in the incidences of allergies, asthma and autoimmune diseases. Results We observed an upregulation of T helper cell signature cytokines during the first 12 months of life, reflecting natural development of adaptive immune responses. During the first years of life, circulating concentrations of epidermal growth factor (EGF) were significantly higher, especially in Russian children compared with Finnish children. The children who developed IgE sensitization showed lower levels of EGF than those without such responses. Conclusion Our results suggest that low circulating EGF levels associate with the risk of allergies possibly via the effects on the epithelial integrity and mucosal homeostasis. Peer reviewed